2013
DOI: 10.1039/c3dt50832c
|View full text |Cite
|
Sign up to set email alerts
|

FRET-based ratiometric fluorescent probes for selective Fe3+ sensing and their applications in mitochondria

Abstract: Efficient ratiometric fluorescent Fe(3+) probes were designed and synthesized by linking a conjugated naphthalene chromophore to a rhodamine platform and a lipophilic triphenylphosphonium (TPP) cation. The probes could sensitively and selectively detect mitochondrial Fe(3+) in living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 39 publications
0
36
0
2
Order By: Relevance
“…[64] Photophysical examinations demonstrated as elective turn-on (10-fold) response,w hile co-staining showed that Mito-CS1 localized in mitochondria in HEK 293T cells ( Figure 4). [66] Upon addition of Fe 3+ ,t he hydrazine interacted with the metal species,t hus opening the ring and restoring the conjugate structure of the rhodamine scaffold. [64] In another case,adeprotection strategy utilizing spirocyclic rhodamine was also applied to develop am itochondriatargeting Cu + probe (14 b,Scheme 3).…”
Section: Mitafps For Metal Ions and The Ph Valuementioning
confidence: 99%
See 2 more Smart Citations
“…[64] Photophysical examinations demonstrated as elective turn-on (10-fold) response,w hile co-staining showed that Mito-CS1 localized in mitochondria in HEK 293T cells ( Figure 4). [66] Upon addition of Fe 3+ ,t he hydrazine interacted with the metal species,t hus opening the ring and restoring the conjugate structure of the rhodamine scaffold. [64] In another case,adeprotection strategy utilizing spirocyclic rhodamine was also applied to develop am itochondriatargeting Cu + probe (14 b,Scheme 3).…”
Section: Mitafps For Metal Ions and The Ph Valuementioning
confidence: 99%
“…Further molecular imaging studies indicated that Mito-CS1 was able to detect changes in the concentration of labile mitochondrial Cu + in both HEK 293T cells and human fibroblasts.I na ddition, Mito-CS1 showed real applications by imaging cytochrome c oxidase 1a nd 2( SCO1 and SCO2) mutations in human fibroblasts,both of which cause variations in the Cu + level. [66] [65] Very recently,C hen et al designed the ratiometric probe RNP1 (15,S cheme 3) for mitochondrial Fe 3+ based on aF RET mechanism.…”
Section: Mitafps For Metal Ions and The Ph Valuementioning
confidence: 99%
See 1 more Smart Citation
“…To further justify these findings, we developed a novel fluorescence iron sensor which measures mitochondrial iron (9). An enhanced far red fluorescence was observed using our RNP1 dye on the basis of FRET mechanism in H9C2 cells treated with DOX (10 M) for 24 h. However, the same dose and duration of the treatment with DOX did not produce a fluorescent signal in our FXN-OE cells in the presence of RNP1 (Fig.…”
Section: Dox-mediated Reduction In Fxn Alters Mitochondrial Iron Homementioning
confidence: 99%
“…In the presence of iron, a deep red fluorescence was obtained. The dye exhibits pseudo-large stokes shift based on a fluorescence resonance energy transfer (FRET) mechanism and the naphthalene chromophore (9). Cultured H9C2 and FXN-OE cardiomyoblasts were treated with or without DOX (10 M) for 24 h and incubated with RNP1 and colocalized with MitoTracker Green FM (1 M) for 30 min.…”
Section: Mitochondrial Iron Detection: Fluorescence Resonance Energy mentioning
confidence: 99%